Effects of plyometrics performed during warm-up on 20 and 40 m sprint performance - Creekmur, C. C.; Haworth, J. L.; Cox, R. H.; Walsh, M. S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Postactivation potentiation in the form of a plyometric during warm-ups have been shown to improve performance in some speed/power events. This study aimed to determine if a plyometric during warm up can increase sprint performance in a 20 and 40 m sprint.